2003
DOI: 10.1242/jcs.00718
|View full text |Cite
|
Sign up to set email alerts
|

RIN3: a novel Rab5 GEF interacting with amphiphysin II involved in the early endocytic pathway

Abstract: The small GTPase Rab5, which cycles between active (GTP-bound) and inactive (GDP-bound) states, plays essential roles in membrane budding and trafficking in the early endocytic pathway. However, the molecular mechanisms underlying the Rab5-regulated processes are not fully understood other than the targeting event to early endosomes. Here, we report a novel Rab5-binding protein, RIN3, that contains many functional domains shared with other RIN members and additional Pro-rich domains. RIN3 displays the same bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
156
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(164 citation statements)
references
References 50 publications
7
156
0
1
Order By: Relevance
“…To date, 21 genes have been strongly associated with LOAD, including endocytosis genes, such as amphiphysin II (BIN1). An amphiphysin II-RIN3 interaction is involved in vesicle trafficking in the early endocytic pathway (21), and it is undoubtedly relevant that amphiphysin II can also bind to CD2AP (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, 21 genes have been strongly associated with LOAD, including endocytosis genes, such as amphiphysin II (BIN1). An amphiphysin II-RIN3 interaction is involved in vesicle trafficking in the early endocytic pathway (21), and it is undoubtedly relevant that amphiphysin II can also bind to CD2AP (50).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the PxPxPR motif, which is characteristic for CBL peptide binding to SH3 domains, we used an in vitro peptide array screen to confirm interaction candidates, many with previously uncharacterized sequence requirements. Among 40 binders reported, including ALIX, BLNK, and zona occludens protein 2 (ZO-2), we followed up on the newly identified RIN3, a RAB5 and RAB31 guanine nucleotide exchange factor involved in endocytosis (21,22), which we identified as a novel interactor in kidney and MCF10A breast cancer cells by several biochemical and biophysical methods.…”
mentioning
confidence: 99%
“…Our previous work suggested that Rin1 is an exchange factor for small GTPase Rab5, whose overexpression stimulates EGF-mediated endocytosis (31). The Rin family now has at least four members, all of which have active Rab5 guanine nucleotide exchange factor domains (32)(33)(34)(35). Subsequent work showed that Rin1 is recruited to the EGFR via its SH2 domain and that it regulates EGF-induced signal transduction (36,37).…”
mentioning
confidence: 99%
“…RLD is followed by a tandem organization of Dbl homology (DH) and pleckstrin homology (PH) domains, which is a hallmark for GEFs for Rho (Ras homologous member) GTPases (14). The C-terminal end of ALS2 harbors a vacuolar protein sorting 9 (VPS9) domain, which has been found in Rab5 (Ras-related in brain 5) GEFs, including Vps9 (15), , RIN1 (17,18), RIN2 (19), and RIN3 (20). In addition, eight consecutive membrane occupation and recognition nexus (MORN) motifs (21) were noted in the region between PH and VPS9 domains.…”
mentioning
confidence: 99%